Long march : a reform agenda for Latin America and the Caribbean in the next decade - Burki, Shahid Javed (World Bank WashingtonUS, 1997)
Proposes a reform agenda to be undertaken by the Latin American and Caribbean countries during the next decade to facilitate economic growth. Identifies reforms required to consolidate macroeconomic stability. Specifies structural reforms to accelerate growth and policies required to broaden the reach of economic growth in order to confront the challenge of poverty in the region.